-3(-4w+1)+15=13

Simple and best practice solution for -3(-4w+1)+15=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-4w+1)+15=13 equation:


Simplifying
-3(-4w + 1) + 15 = 13

Reorder the terms:
-3(1 + -4w) + 15 = 13
(1 * -3 + -4w * -3) + 15 = 13
(-3 + 12w) + 15 = 13

Reorder the terms:
-3 + 15 + 12w = 13

Combine like terms: -3 + 15 = 12
12 + 12w = 13

Solving
12 + 12w = 13

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 12w = 13 + -12

Combine like terms: 12 + -12 = 0
0 + 12w = 13 + -12
12w = 13 + -12

Combine like terms: 13 + -12 = 1
12w = 1

Divide each side by '12'.
w = 0.08333333333

Simplifying
w = 0.08333333333

See similar equations:

| 4=2(u-4)-8u | | 12.48+0.11=13.23+0.09 | | 8x-4y=-20 | | 21+2(21+3)+(4*21-5)=c | | 6-8(1+6x)=-2-4x | | 1/2(-2)= | | -5(-17-13d)=-4(10-15d) | | 5(2n-4)-3=-36-3n | | -36-4a=-4(8a-5) | | 4x+3+4x=-15 | | 0=-8m^2-2m+2 | | -15s=-75 | | -3/2m+2/3m=-1/2(1/2m-3/2)-8/3(1/2m+1) | | x-(12)=-4 | | 2x+(2/(2x-12)) | | -7(4t+14)=-20-15t | | -7x=-28+11-4 | | y-19.25=x^2+6x+30.25 | | 3-x=2(1-4x)-6 | | 7t-12-2t=9+5t | | 2x+(2/2x-12) | | 2.5x+.5x=6+3.5 | | -(-20-4s)=-2(s+8) | | -8r=4(r-3) | | -50=19+y | | -5n-10=-(8n-1)-8n | | y=(x-2)-1 | | -(30)-(10)-43= | | 25200*(1/9) | | 80=1.8C+32 | | -255=-15k | | 10h=2(4h+13) |

Equations solver categories